PENGARUH VARIASI BOBOT ROLLER WEIGHT CVT TERHADAP AKSELERASI SEPEDA MOTOR HONDA VARIO 150 - Riyadi; Darwin Rio Budi Syaka; Arya Firmansyah (Universitas Negeri Jakarta, 2023)
Based on the experience of automatic motorcycle users Honda Vario 150, the motorcycle has several weaknesses, but one of the weaknesses that often occurs is the slow acceleration of the motorcycle from low to medium speed. CVT transmission system (Continuously Variable Transmission) affects the slow acceleration of a motorcycle from low to medium speed. The purpose of this study is to analyze the results of testing the use of roller weights with standard weights (18 g), 16 mix standard, and 16 g to get the value of the best acceleration on a dead motorcycle c Honda Vario 150. The research method used is an experimental research method using two research methods, namely testing with a dynamometer and testing with acceleration measurements with logger pro software. The use of a standard roller weight (18 g) is the roller weight with the fastest acceleration on a Honda Vario 150 motorcycle. This is evidenced by an average acceleration of 2.98 m/s2 . While the roller weight of 16 mix standard and 16 g experienced a decrease in acceleration. For roller weight 16 mix standard, there was a decrease in acceleration of 15.44% with an average acceleration of 2.52 m/s2 . And on the 16 g roller weight, there is a decrease in acceleration of 28.86 % with an average acceleration of 2.12 m/s2.